Hubungan Tingkat Spiritual dan Religiusitas dengan Tekanan Darah pada Lansia Hipertensi - Anisa Kirnawati; Latifa Aini Susumaningrum; Hanny Rasni; Tantut Susanto; Diana Kholida (Poltekkes Kemenkes Jakarta III, 2021)
The aging process which happens in elder people has effects on blood pressure. The well maintenance of blood pressure will impact on elder people’s daily activities, included in increasing spirituality. This is the one factor which can control over blood pressure. This research uses cross sectional design with purposive sampling method which had been implemented for 70 elder people and got 33 respondents. Data were collected by giving questionnaire such as elder people charactheristic, Daily Spiritual Experimental Scale (DSES) and Sphygnomanometer used to measure blood pressure. Chi-Square Test by 0,05 significance values is examined as data analysis. The result indicates that the average value of spirituality level is Md 39 + 36-47,5 and the average value of blood pressure level is 160,52 systole and 97,09 diastole. Thus, the results also reveals relationship betwen spirituality level and blood pressure (p value 0,002). This study significance shows that the higher level of spirituality is, the easily elder people manage blood pressure. Therefore, elder people living in nursing home should increase the spirituality level or their religion to control blood pressure.